A chromosome‐level genome assembly of radish (Raphanus sativus L.) reveals insights into genome adaptation and differential bolting regulation. Issue 5 (2nd February 2023) - Xu, Liang; Wang, Yan; Dong, Junhui; Zhang, Wei; Tang, Mingjia; Zhang, Weilan; Wang, Kai; Chen, Yinglong; Zhang, Xiaoli; He, Qing; Zhang, Xinyu; Wang, Kai; et al.
Summary: High‐quality radish ( Raphanus sativus ) genome represents a valuable resource for agronomical trait improvements and understanding genome evolution among Brassicaceae species. However, existing radish genome assembly remains fragmentary, which greatly hampered functional genomics research and genome‐assisted breeding. Here, using a NAU‐LB radish inbred line, we generated a reference genome of 476.32 Mb with a scaffold N50 of 56.88 Mb by incorporating Illumina, PacBio and BioNano optical mapping techniques. Utilizing Hi‐C data, 448.12 Mb (94.08%) of the assembled sequences were anchored to nine radish chromosomes with 40 306 protein‐coding genes annotated. In total, 249.14 Mb (52.31%) comprised the repetitive sequences, among which long terminal repeats (LTRs, 30.31%) were the most abundant class. Beyond confirming the whole‐genome triplication (WGT) event in R. sativus lineage, we found several tandem arrayed genes were involved in stress response process, which may account for the distinctive phenotype of high disease resistance in R. sativus . By comparing against the existing Xin‐li‐mei radish genome, a total of 2 108 573 SNPs, 7740 large insertions, 7757 deletions and 84 inversions were identified. Interestingly, a 647‐bp insertion in the promoter of RsVRN1 gene can be directly bound by the DOF transcription repressor RsCDF3, resulting into its low promoter activity and late‐bolting phenotype of NAU‐LB cultivar. Importantly, introgression of this 647‐bp insertion allele, RsVRN1 In‐536, into early‐bolting genotype could contribute to delayed bolting time, indicating that it is a potential genetic resource for radish late‐bolting breeding. Together, this genome resource provides valuable information to facilitate comparative genomic analysis and accelerate genome‐guided breeding and improvement in radish.